Carbon Sequestration Potential of Kpashimi Forest Reserve, Niger State, Nigeria - Jibrin, Abdullahi; Zubairu, Sule Mohammed; Abdulkadir, Aishatu; Kaura, Sakoma J; Baminda, Amos Bitrus (International Journal of Geography and Geology, 2014)
This study provides a preliminary assessment of the biophysical potential for carbon sequestration. Quantification of carbon stock and estimation of carbon sequestration potential was carried out in the Kpashimi Forest Reserve, Niger state, Nigeria. Carbon stock was measured in the six vegetation communities existing in the study area. Forty-eight randomly selected 20 x 20 metre quadrats were established wherein data was collected from the main forest carbon pools; including above ground tree, below ground root, undergrowth (shrub grasses), dead wood, litter and soil organic carbon. Biomass of the respective pools was quantified by destructive sampling and use of allometric equations. Thereafter, biomass values were converted to carbon stock equivalent. Four satellite imageries TM, SPOT, ETM+, and NIGERIASAT-1 of 1987, 1994, 2001 and 2007 respectively were used to estimate vegetation cover and carbon stock change over 20 years. The results showed that average carbon stock density (Mg C/ha) of the vegetation communities was in the decreasing order; Riparian forest (123.58 ± 9.1), Savanna woodland (97.71 ± 8.2), Degraded forest (62.92 ± 6.1), Scrubland (36.28 ± 4.1), Grassland (18.22 ± 5.1), and bare surface (9.31 ± 3.1). Deforestation and forest degradation between 1987 and 2007 have resulted in emission of 240.2 Mg (ton) C ha-1 at an annual rate of 12.01 Mg C ha-1. This suggests that the study site has carbon sequestration potential of 240.2 Mg C ha-1 based on its capacity to increase carbon stock through restoration; back to speculated 1987 levels and even higher. Thus, the study recommends the need to analyse carbon offset project feasibility in the study area.